Metabolic cities of the future. Between Agriculture and Architecture - Leonardo Zaffi; Michele D'Ostuni (Agathón)
The constant migratory phenomena and the displacement of part of the world’s population from the countryside to the city are bringing great part of the agricultural workforce in the big cities, changing their work sector from agriculture to industry. In this context, theorists and promoters of urban farming have seen in this industry a powerful tool to find spaces suitable for cultivation within the urban fabric, while promoting a new green development of the city. Resuming the fascination of mega-structures proposed in the second half of the twentieth century, in the gap between utopia and dystopia, this essay investigates models and solutions for the integration of agricultural production systems within above-ground architectures, designed to meet the demand for new living spaces in future ultra-populated cities, as a possible response to the soil impoverishment that made it difficult to implement traditional farming systems in and around urban areas.